Cândido Lusitano. As Ifigénias de Eurípides - Inácio, Ana (2022)
The main purpose of this volume is the transcription of the translations / adaptations of Euripides’ Iphigenia in Aulis and Iphigenia among the Taurians, made by Cândido Lusitano. Preceding the text of the plays, transcribed from a still unpublished manuscript, the book opens with an introductory study, focused on two essential topics: the Greek tradition of the myth of Iphigenia and the specificity of the Euripidean versions; the treatment of the myth of Iphigenia, in the form of translation and adaptation, among the members of the Arcádia Lusitana.